Pengembangan Website Desa Wisata Sebagai Media Informasi Wisatawan Pada Desa Temesi - Ambara, I Gede Yoga Agus; Paramitha, A.A. Istri Ita; Putri, I Gst. Agung Pramesti Dwi (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
The tourism industry is undergoing significant changes with the advancement of digital technology, known as digital tourism. Digitalization has changed the way tourist destinations are promoted, accessed, and managed, including through the concept of rural tourism or tourism villages. Temesi Village in Gianyar Regency, Bali, has great natural and cultural tourism potential. However, to optimize this potential, digital media is needed, such as website creation. The WordPress platform was chosen for its advantages, including a large user community, ease of use, design flexibility, and data security. This step aligns with the digital village program supported by the Community Empowerment Agency and Primakara University. It is hoped that the creation of this website will introduce and promote the tourism potential of Temesi Village to the general public and tourists, as well as support sustainable tourism development in the area.